INFLUENCIA DEL MÉTODO DE ENSEÑANZA LA GLOBALIDAD EDUCATIVA EN EL RENDIMIENTO ACADÉMICO DE LOS ALUMNOS, PARA LA ASIGNATURA DE BIOLOGÍA, EN EL COLEGIO NACIONAL MIXTO FELIPE SANTIAGO ESTENÓS - Posso Rojas, Mario (2019)
The Method of Education Globalidad Educativa (M.E.G.E), - characterized by the establishment of nexuses between the different disciplines on the part of the pupils in a certain subject, pertaining to a didactic unit of the subjet of Biology it is an alternative to improve the academic yield. Using t distribution, for samples of variance population not known obtained that the theoretical value of t, for a margin of error of 5% and 79 degrees of freedom, is t0 = 1,6641 the one that to the being resisted with the calculated value of t = 4,0481, this one is greater than the value of theoretical t, therefore we accepted the alternating hypothesis. When culminating the work of investigation was obtained that the students of 4to° C of the subjet of Biology, besides to obtain a greater academic yield, have promoted their intellectual capacities, motor, artistic and ethical.